The most useful technological tools utilized for english language teaching - Hernández Rivera, Dennice Estephanie; Bermúdez de Rivas, Rubidia Esmeralda (2024)
Education has experienced several changes during the last 3 years; one of those changes is the raise of virtual education. For this reason, teachers have been obliged to develop and manage virtual classrooms using two important tools: Internet connection and a phone or computer. I order to approach virtual classrooms, it is very important for teachers to be up-to-date on the use of apps and websites that can help them to develop understandable and interesting classes. There are several apps and websites teachers can use to develop their classes: They can find apps to develop presentations, to create conferences, to have practice activities, to have production activities, to make evaluations and exams, etc. The only thing they need to do is to make a little research on how to use them and start to make use of such apps and websites. Key words: Virtual environments ; Technological tools ; Education ; Classroom management ; E-learning ; Synchronous ; Asynchronous ; Teaching.